The Effect of Prebiotic Starch and Pectin from Ambon Banana Peel (musa acuminata aaa) on the Growth of Skin Microbiota Bacteria In Vitro - Rusdi, Bertha; Aryani, Ratih; Yuniarni, Umi (Pharmacology and Clinical Pharmacy Research, 2023)
Propionibacterium acnes is a bacteria which causes acne. This bacteria is hypothesized to be inhibited by Staphylococcus epidermidis. Prebiotics have been shown to enhance the number of S. epidermidis and decrease the growth of P. acnes. The prebiotic action of starch and pectin from diverse plant sources is known in the skin microbiome. The prebiotic activity of Ambon banana peel starch and pectin on skin microbiota has not been researched. This study aims to investigate the prebiotic activity of starch and pectin from Ambon banana peels on skin microbiota, represented by S.epidermidis and P.acnes. The results showed that starch, and pectin have a prebiotic activity because they promoted the growth of S. epidermidis while suppressing the growth of P. acnes. P. acnes inhibitor percentages were 1.62% for starch and 65.07% for pectin. Negative inhibition values were -184.95% for starch and -5.80% for pectin suggesting an increase in S. epidermidis proliferation.